VIDEO GAME EDUKATIF TERHADAP KEMAMPUAN MENGENAL ANGGOTA TUBUH MANUSIA PADA ANAK TUNARUNGU KELAS I - HIRNANDIN, ASTRI; , WAGINO (Jurnal Pendidikan Khusus, 2018)
ABSTRACTEducative video games recognizing the part of human body is a process of using thought and game mechanics to solve problems through computers that attract deaf children to learn. So that deaf children will be better able to pay attention and receive visual information learning through the relationship between the content of subject matter with the real world.The purpose of this study was to determine whether or not the effect of educative video games toward ability of recognizing the part of human body to deaf children of class I in SDLB-B Karya Mulia 1 Surabaya.This research uses quantitative approach of pre experimental research type and one group pre test ? post test design. The statistic technique applied in data analysis was wilcoxon match pairs test. The data collection techniques were test and observationThe research result indicated that Zh = 2,66 was greater than critical value of Z table 5%, Zt = 1,96 (Zh> Zt) so Ho is rejected and Ha accepted. The use of educative video games significantly influences toward ability of recognizing the part of human body to deaf children of class I in SDLB-B Karya Mulia 1 Surabaya. Keywords : Educative video game, part of body